Expanding the Amiseginae: remarkable new Cretaceous-age fossils shed light on the early diversification of a highly specialized clade of cuckoo wasps (Hymenoptera: Chrysididae) - Lucena, Daercio A A [UNESP]; Melo, Gabriel A R (Oxford University Press (OUP), 2025)
Abstract The oldest representatives of the amisegine cuckoo wasps are described from inclusions in mid-Cretaceous Burmese amber. Four monotypic new genera are described and illustrated: †Cenomanisega krombeinigen. et sp. nov., †Cretamisega mandibularisgen. et sp. nov., †Protognathosega depilisgen. et sp. nov., and †Telistosega intermediagen. et sp. nov. Additionally, †Miracorium amicasp. nov. is described and illustrated based on the discovery of the first female in the genus †Miracorium. We used Bayesian inference to establish the phylogenetic position of the new fossils within Chrysididae. The new fossils exhibit specialized modifications in the female mouthparts and apparatus for oviposition, which are consistent with the feeding and egg-laying habits observed in the modern Amiseginae. Our findings suggest that these traits evolved ≥100 Mya and might have been crucial in the early diversification of the clade as specialized parasitoids of walking stick eggs.